Tissue engineering scaled-up anatomically shaped osteochondral constructs for joint resurfacing - Mesallati, Tariq (Trinity College (Dublin, Ireland). Department of Mechanical and Manufacturing Engineering, 2014)
Partial and total joint replacements are the only surgical procedures currently available to treat articular cartilage degeneration associated with degenerative diseases such as osteoarthritis (OA). While these procedures are well established, they are not without limitations and failures are not uncommon. Joint replacement prostheses also have a finite lifespan making them unsuitable for the growing population of younger and more active patients requiring treatment for OA. In recent years there has been increased interest in the use of cell and tissue engineering based therapies for the treatment of focal cartilage defects. These therapies aim to regenerate or replace damaged tissues through a combination of cells, three-dimensional scaffolds and signalling molecules. While significant progress has been made in this field, realizing an efficacious therapeutic option for the treatment of OA remains elusive and is considered to be one of the greatest challenges in the field of orthopaedic medicine.
Keywords: Bioengineering, Ph.D.; Ph.D. Trinity College Dublin